2016
DOI: 10.1016/j.ijpara.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus sequence typing of Dientamoeba fragilis identified a major clone with widespread geographical distribution

Abstract: The flagellated protozoan Dientamoeba fragilis is often detected in humans with gastrointestinal symptoms, but it is also commonly found in healthy subjects. As for other intestinal protozoa, the hypothesis that genetically dissimilar parasite isolates differ in their ability to cause symptoms has also been raised for D. fragilis. To date, only two D. fragilis genotypes (1 and 2) have been described, of which genotype 1 largely predominates worldwide. However, very few markers are available for genotyping stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…AY730405.1 and FJ649228.1). These results indicated low level of polymorphism, in agreement with recent studies [47,49].…”
Section: Discussionsupporting
confidence: 93%
“…AY730405.1 and FJ649228.1). These results indicated low level of polymorphism, in agreement with recent studies [47,49].…”
Section: Discussionsupporting
confidence: 93%
“…fragilis , G1 and G2, have been described [ 30 ]. This low genetic diversity has been recently confirmed by multilocus sequence typing of isolates from different regions of the world [ 37 ]. This study showed the worldwide predominance of G1 and the relative rarity of G2.…”
Section: Discussionmentioning
confidence: 81%
“…Due to the presence of specific virulence factors, ETEC, EIEC, EAEC and EHEC are all being recognized as pathogenic diarrhoea-causing variants of the generally harmless human commensal E. coli (Hart et al ., 1989; Robins-Browne and Hartland, 2002). Based on 18S rRNA sequence differences, two major D. fragilis genotypes have been described, but the overall significance with regard to pathogenicity (if any) is unclear (Johnson and Clark, 2000; Peek et al ., 2004; Windsor et al ., 2006; Hussein et al ., 2009; Dunwell, 2013; Cacciò et al ., 2016). Barratt et al detected the presence of RNA and coding genes in the transcriptome of D. fragilis known to be possible cytotoxic virulence factors such as cysteine peptidases, saposin-like proteins and a leukotriene A4 hydrolase-like peptidase, pointing to a pathogenic character of D. fragilis (Barratt et al ., 2015).…”
Section: Introductionmentioning
confidence: 99%